Relaxation of active acoustic emission sources during the natural aging of A³B⁵ epitaxial structures - Veleschuk, V.P.; Lyashenko, O.V. (Functional Materials, 2004)
The aging processes of A³B⁵ epitaxial light-emitting structures have been shown to reduce acoustic emission (AE) intensity, AE count, and to raise the AE onset threshold while an increased change rate of the direct current through junction results in that AE onset threshold becomes shifted towards lower currents, the failure currents drop, and AE intensity and AE count increase.